1998
DOI: 10.1523/jneurosci.18-24-10749.1998
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Inhibits GABA Excitatory Activity in Developing Neurons

Abstract: In contrast to the mature brain, in which GABA is the major inhibitory neurotransmitter, in the developing brain GABA can be excitatory, leading to depolarization, increased cytoplasmic calcium, and action potentials. We find in developing hypothalamic neurons that glutamate can inhibit the excitatory actions of GABA, as revealed with fura-2 digital imaging and whole-cell recording in cultures and brain slices. Several mechanisms for the inhibitory role of glutamate were identified. Glutamate reduced the ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 62 publications
0
27
0
1
Order By: Relevance
“…On the other hand, as compared with the developmental variations of glutamate and glycine, significant decreases in taurine levels were also observed during three stages: between E15 and E16, between P3 and P7, and in the young adult age, which seems to reinforce the role of taurine in spinal cord neurotransmission. Taurine is known to activate glycine and GABA A receptors during early neocortical development; various reports have demonstrated that these receptors have an excitatory influence in the developing neocortex, leading to increased synaptic activity and elevation of intracellular calcium [11,21,35,69]. As shown in table 1, the ratio of taurine to glutamate in the developing spinal cord varied from 2-to 4-fold, and the ratio of taurine to glycine, from 2-to 6-fold; in the adult stage, both ratios gave values of 1:1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, as compared with the developmental variations of glutamate and glycine, significant decreases in taurine levels were also observed during three stages: between E15 and E16, between P3 and P7, and in the young adult age, which seems to reinforce the role of taurine in spinal cord neurotransmission. Taurine is known to activate glycine and GABA A receptors during early neocortical development; various reports have demonstrated that these receptors have an excitatory influence in the developing neocortex, leading to increased synaptic activity and elevation of intracellular calcium [11,21,35,69]. As shown in table 1, the ratio of taurine to glutamate in the developing spinal cord varied from 2-to 4-fold, and the ratio of taurine to glycine, from 2-to 6-fold; in the adult stage, both ratios gave values of 1:1.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of synaptogenesis in spinal motoneurons occurs at E16-E17, when most of the synaptic contacts are formed by glycinergic and GABAergic neurons; excitatory synapses are established on all motoneurons by E19 [33]. The pattern of functional expression suggests that, during the embryonic period until at least 1-2 days after birth, glycine and GABA generate chloride-dependent membrane depolarizations in spinal motoneurons, but it is not known at what age the agonists begin to produce membrane hyperpolarizations [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…A shutter blocked the fluorescent light between data captures. In time-lapse recordings, one image was saved every 4 s. During recording, slices were maintained in a HEPES buffer (44). After we recorded a control baseline fluorescence, the cells were stimulated with a micropipette as described elsewhere (12).…”
Section: Methodsmentioning
confidence: 99%
“…Alterations in glutamate levels may alter several processes that are dependent on normal levels of this neurotransmitter, such as regulation of the nervous system development (McDonald and Johnston, 1990;Komuro and Rakic, 1993;Johnston, 1995;LaMantia, 1995;Vallano, 1998), neuronal migration (Komuro and Rakic, 1993;Rossi and Slater, 1993), outgrowth of neuronal processes (Pearce et al, 1987;Rajan et al, 1999), normal organization of the somatosensory cortex (Fox et al, 1996) as well as GABAergic activity (Van den Pol et al, 1998). In line with the importance of the glutamatergic signaling, both overstimulation (Johnston, 1995) and understimulation of glutamate receptors are harmful to the developing brain (Ikonomidou et al, 2000).…”
Section: Discussionmentioning
confidence: 99%